Implementasi Reward Asyik dalam Meningkatkan Kemandirian Anak Usia Dini - Nurfaidah, Nida; Watini, Sri (Universitas Cokroaminoto Palopo, 2023)
The purpose of this study is to evaluate how well ASYIK Rewards work to increase young children's learning independence. There is still a deficiency of independence in the educational setting of Ar-Raudhatul Ulum Kindergarten, particularly in autonomous study. Teachers must find workable solutions to get around this. At Ar-Raudhatul Kindergarten, one useful strategy might boost students' learning freedom. The second goal of In early childhood learning activities where there are problems with establishing self-confidence, the goal of this study is to increase independence. Those who had previously been bashful and hesitant to communicate with others or answer questions in front of friends and professors now feel comfortable and capable of providing solid, concise answers to any queries they pose online. Twenty students from group A of the Ar-Raudhatul Ulum Kindergarten served as the research subjects. With each signal, the Safe, Happy, Confident, Innovative, and Creative characteristics are the criteria that determine the evaluation score for early childhood learning independence with the ASYIK Reward. For the five observation scores, very good is represented by (√), good by (+), and minus by (-). There is an increase in scores following use, according to the findings of cycles I and II of the pre-cycle research. According to the research findings, the class completion scores from pre-cycle to cycles I and II seem to have increased. Prior to using the